Community participation in Felcra oil palm plantation : a case study of Kampung Pinang, Kota Samarahan division - Wong, Tat King (Faculty of Social Sciences, 2005)
The main objective of the study is to assess socio-economic impacts of participation in oil palm plantation scheme, Kampung Pinang, Kota Samarahan and alternatives of the community to sustain, their lives in the village. The specific objectives are 1) To determine participants' demographic characteristic; 2) To determine socio-economic data of the participants; 3) To study the impact of community participation in oil palm plantation; 4) To assess involvement of the participants in other land use; and 5) To assess level of participation of the participation.